2017
DOI: 10.5222/gkdad.2017.020
|View full text |Cite
|
Sign up to set email alerts
|

The use of cerebral oximetry (Fore-Sight) in the follow-up hypoperfusion in pediatric cardiac surgery

Abstract: ÖZ Amaç

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…13 In the study of Işıldak et al evaluating the use of cerebral oximetry in hypoperfusion monitoring in pediatric cardiac surgery; they concluded that intraoperative monitoring of perfusion with cerebral oximetry during congenital heart surgery is a valuable indicator and they also report that right and left cerebral oximetry values have fallen in cases of tissue oxygenation was impaired (ex: hypotension, hemodilution, hypovolemia, anemia) and they determined that the values were corrected when the precautions were taken. 20 In our study, rSO 2 values decreased to 58% and 59% in 2 patients during hypothermia (T3) period. In these cases, the pump flow was increased and cerebral oxygenation of the patients was kept above 60%.…”
Section: Discussionsupporting
confidence: 44%
“…13 In the study of Işıldak et al evaluating the use of cerebral oximetry in hypoperfusion monitoring in pediatric cardiac surgery; they concluded that intraoperative monitoring of perfusion with cerebral oximetry during congenital heart surgery is a valuable indicator and they also report that right and left cerebral oximetry values have fallen in cases of tissue oxygenation was impaired (ex: hypotension, hemodilution, hypovolemia, anemia) and they determined that the values were corrected when the precautions were taken. 20 In our study, rSO 2 values decreased to 58% and 59% in 2 patients during hypothermia (T3) period. In these cases, the pump flow was increased and cerebral oxygenation of the patients was kept above 60%.…”
Section: Discussionsupporting
confidence: 44%